Antioxidant and antigenotoxic properties of CeO2 NPs and cerium sulphate: Studies with Drosophila melanogaster as a promising in vivo model. Issue 6 (September 2015) - Alaraby, Mohamed; Hernández, Alba; Annangi, Balasubramanyam; Demir, Esref; Bach, Jordi; Rubio, Laura; Creus, Amadeu; Marcos, Ricard
Abstract Although in vitro approaches are the most used for testing the potential harmful effects of nanomaterials, in vivo studies produce relevant information complementing in vitro data. In this context, we promote the use of Drosophila melanogaster as a suitable in vivo model to characterise the potential risks associated to nanomaterials exposure. The main aim of this study was to evaluate different biological effects associated to cerium oxide nanoparticles (Ce-NPs) and cerium (IV) sulphate exposure. The end-points evaluated were egg-to-adult viability, particles uptake through the intestinal barrier, gene expression and intracellular reactive oxygen species (ROS) production by haemocytes, genotoxicity and antigenotoxicity. Transmission electron microscopy images showed internalisation of Ce-NPs by the intestinal barrier and haemocytes, and significant expression of Hsp genes was detected. In spite of these findings, neither toxicity nor genotoxicity related to both forms of cerium were observed. Interestingly, Ce-NPs significantly reduced the genotoxic effect of potassium dichromate and the intracellular ROS production. No morphological malformations were detected after larvae treatment. This study highlights the importance of D. melanogaster as animal model in the study of the different biological effects caused by nanoparticulated materials, at the time that shows its usefulness to study the role of the intestinal barrier in the transposition of nanomaterials entering via ingestion.